Wina bez prawa Struktura nowej iluzji - Leder, Andrzej (Śląskie Studia Polonistyczne, 2015)
Basing his argumentation on Freud’s essay Civilisation and Its Discontents, the author poses a question about the essence of suffering which appears when the Law of the Father is suspended and no longer protects against the death drive. The author formulates a thesis that in the contemporary social space, abandoned by the Law of the Father, it is disciplinary practices that play a key regulative role, pretending to form the relations based on the law. These practices transform the drive energy of Thanatos, which then finds its embodiment in the everyday lifelessness of bureaucracy, the coolness of rules and the excess hidden beneath them. The answer to this situation is Eros, which drives people to community – yet not so much in the form of a family as of an infinite and noneconomic continuum of local games of love and death.